THE ROLE OF GREEN INFRASTRUCTURE AND SURAMADU BRIDGE IN SUPPORTING SUSTAINABLE DEVELOPMENT AT TRUNOJOYO UNIVERSITY MADURA - Tesalonika Dwi Gres Sitio; Saptia Wahyuni; Bima Kurniawan (Jurnal Media Akademik (JMA), 2024)
Sustainable development in Madura, particularly at Universitas Trunojoyo Madura (UTM), is an increasingly relevant topic along with the increasing number of students and infrastructure development around the campus. This research aims to evaluate the implementation and challenges of sustainable development at UTM, focusing on faculty improvements, the construction of boarding houses, cafes around campus, and the impact of the Suramadu Bridge on student mobility. Related to sustainability programs and infrastructure at UTM. The results show that UTM has made various efforts to improve faculty facilities, such as improving the quality of buildings, procuring environmentally friendly facilities, and implementing energy-saving technologies. In addition, the increase in the number of students has encouraged the construction of boarding houses around campus, which has the potential to have both positive and negative impacts on the environment. Many new boarding houses are built with designs that take into account sustainability aspects, but some still do not meet good environmental standards. The development of cafés around campuses has also become an important phenomenon, given their role as centers of social and economic activity for students. Some cafés have started to implement environmentally friendly practices, such as the use of recycled building materials, good waste management, and the provision of organic food. However, there are still challenges in raising café owners' awareness of the importance of sustainable practices. In addition, the existence of the Suramadu Bridge has facilitated the mobility of students living in Surabaya and surrounding areas to commute to UTM. The bridge not only reduces travel time but also provides easier and faster access, thus increasing student participation in academic and non-academic activities. It recommends increased collaboration between the university, government and community to create a more sustainable environment. Measures such as increased environmental education for students, incentivizing landlords, and encouraging them to build more sustainable neighborhoods are important.